Proporción de harina de sangre y harina de pescado en el rendimiento productivo del pollo Cobb 500 en Zúngarococha - Pérez Correa, Jedidías (2025)
In poultry production, the cost of protein inputs such as fishmeal presents a significant challenge for producers. Blood meal is proposed as an alternative substitute, with the aim of evaluating its effect on the productive performance of Cobb 500 chicken. This research was developed using a completely randomized design (DCA), applying five dietary treatments with flour inclusion levels. of 0%, 25%, 50%, 75% and 100% blood, in a total of 100 birds. The results showed that the T2 Treatment, with an inclusion of 50% of blood meal, was the most effective in terms of feed efficiency and feed conversion, standing out as the treatment with the highest use of feed without compromising the health of the birds. Analyses of final weight and weight gain revealed no significant differences between treatments, suggesting that blood meal can partially or fully replace fishmeal without negatively affecting chicken growth. It is concluded that blood meal is a viable alternative in poultry production, recommending its application in different production contexts to validate its benefits. Future research could focus on other local protein substitutes, which could diversify sustainable and cost-effective feed options in the poultry sector.